The General Weakness Syndrome Therapy (GymNAST) study: protocol for a cohort study on recovery on walking function. Issue 10 (24th October 2014) - Mehrholz, Jan; Mückel, Simone; Oehmichen, Frank; Pohl, Marcus
Abstract : Introduction: Critical illness myopathy (CIM) and polyneuropathy (CIP) are common complications of critical illness that frequently occur together. Both cause so called intensive care unit (ICU)-acquired muscle weakness. This weakness of limb muscles increases morbidity and delay rehabilitation and recovery of walking ability. Although full recovery has been reported people with severe weakness may take months to improve walking. Focused physical rehabilitation of people with ICU-acquired muscle weakness is therefore of great importance. However, although physical rehabilitation is common, detailed knowledge about the pattern and the time course of recovery of walking function are not well understood. Therefore, the aim of the General Weakness Syndrome Therapy (GymNAST) study is to describe the time course of recovery of walking function and other activities of daily living in these patients. Methods and analysis: We conduct a prospective cohort study of people with ICU-acquired muscle weakness with defined diagnosis of CIM or CIP. Based on our sample size calculation, approximately 150 patients will be recruited from the ICU of our hospital in Germany. Amount and content of physical rehabilitation, clinical tests for example, muscle strength and motor function and neuropsychological assessments will be used as independent variables. The primary outcomes will include recovery of walking function and mobility. Secondary outcomes will include global motor function, activities in daily life and participation. Ethics and dissemination: The study is being carried out in agreement with the Declaration of Helsinki and conducted with the approval of the local medical Ethics Committee (Landesärztekammer Sachsen, Germany, reference number EK-BR-32/13-1) and with the understanding and written consent of each patient's guardian. The results of this study will be published in peer-reviewed journals and disseminated to the medical society and general public.